Entrepreneurial passion: A key driver of social innovations for tourism firms - Dias, Á.; Hallak, R.; Patuleia, M. (Entrepreneurship Research Journal, 2025)
Small and medium tourism enterprises (SMTEs) play a vital role in the sustainability and innovation of tourism destinations. Although their role in the sustainability of destinations has received much attention, research focusing on the antecedents of their social innovation practices remains limited. Drawing on theories on entrepreneurship and social innovation, this study contributes to the body knowledge through an empirical analysis of the factors that drive the social innovations of tourism entrepreneurs. For this purpose, a mixed method approach is conducted which includes an e-survey of tourism entrepreneurs (analysed using PLS-SEM, NCA and IPMA) followed by in-depth interviews to gain additional insights. The results showed that 68 % of the SMTEs pursue social development objectives, and 44 % seek opportunities to improve the social conditions of the community in which the firm operates. The results also reveal that entrepreneurial self-efficacy, community attachment and entrepreneurial passion positively influence social innovations, however, entrepreneurial passion is a ‘necessary condition’ for achieving social innovation outcomes. Research also found that ‘opportunity perception’ has an indirect effect on social innovations that is mediated by entrepreneurial self-efficacy. The results provide important insights for the development of social innovation in the context of tourism entrepreneurs, with practical implications for local governments and destination authorities in supporting entrepreneurship and sustainability.